Case control study of supervised and unsupervised medical abortion in first trimester of pregnancy - Verma, Shikha; Ranjan, Rita; Batra, Megha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The MTP act of India 1971 provides for the termination of pregnancy up to 20 weeks of gestation, by a registered medical practitioner, provided all the prerequisites are fulfilled. The objective of this study was to conduct case control study of supervised and unsupervised medical abortion in first trimester of pregnancy. Methods: A case control study was conducted with two groups of patients with period of gestation <9 weeks. Case group consist of 30 patients presenting to emergency department with unsupervised intake of medical abortion pill. Control group consist of 30 patients presenting to family planning outpatient department want medical abortion pill under supervision. The main outcome variables were comparison of success rate, failure rate, complications like pain, fever, heavy bleeding, shock, requirement of blood transfusion. Interventions required were compared in both the groups in terms of medical management, surgical evacuation and laparotomy. Results: In our study, the success rate achieved in terms of complete abortion was 66.7% in the supervised and 13.3% in the unsupervised group with (p value <0.001). The complication rate was 60% in the supervised group in contrast to 93.3% in the unsupervised group. 56.7% patients in unsupervised group required blood transfusion which was nil in supervised groups. 71.4% patients in the supervised group did not require intervention. In the unsupervised group, 13.8% required medical management, 65.5% required surgical evacuation and 6.7% had to undergo laparotomy for ectopic pregnancy. Conclusions: In present study we conclude that first trimester medical abortion under supervision is more effective, safe and convenient as compared to unsupervised medical abortion. We recommend that government must stop over the counter sell of medical abortion pills.